Partial migration of grey mullet (Mugil cephalus) on Australia's east coast revealed by otolith chemistry. (August 2016) - Fowler, Ashley M.; Smith, Shannen M.; Booth, David J.; Stewart, John
Abstract: Partial migration affects the ecology and evolution of animal populations, and is an important consideration for the management of harvested species, yet the phenomenon is understudied in fish. We provide the first insights into partially diadromous migration of grey mullet ( Mugil cephalus ) in Australia by examining the otolith chemistry of old individuals (aged 7–10 years) from two regions on the east coast. Strontium and Barium concentrations were measured across the otolith using laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) and indicated considerable diversity in migratory histories among individuals. Only 15% of individuals made repeated movements from estuaries to the marine environment, consistent with the annual spawning run in the region. The remainder either made irregular movements between salinity environments (70%), or resided in estuaries or fresh water for their entire life following the early juvenile stage (15%). The patterns are consistent with 'skipped spawning' partial migration, where a proportion of the mature population forgoes spawning each year. If confirmed, the behavior may afford the east coast population of M . cephalus some resilience to fishing pressure on the annual spawning run. Highlights: Diverse migratory histories were found for grey mullet on Australia's east coast. Residents did not enter the spawning (marine) environment for up to 7 years. Migratory patterns are consistent with skipped spawning partial migration.